Bahasa Indonesia Bahasa Indonesia - Herliani; Lambang Subagiyo; Sukemi (Jurnal Penelitian Pendidikan IPA, 2023)
Anchored by the interview analysis, the present study explored students’ perceptions of blended learning enactment in Indonesian science classrooms. Data were garnered through questionnaires and semi-structured interviews focusing on students' perceptions of the benefits and challenges of adopting Blended Learning in science classes. Findings suggest that the benefits geared by blended learning in science classes include training students’ learning independence, increasing students’ understanding of science and technology, increasing students’ learning effectiveness, and providing students with a variety of learning experiences. Meanwhile, the challenges depicted in blended learning include practicum activities, internet problems, and economic condition. This study pictured blended learning as an alternative learning method for teachers and students.